An Improvement of Street Food Vender in Thailand - Chantawibul, Amporn; Damapong, Sanga (Journal of Health Science of Thailand, 2019)
Street food vendor is a category of small-sized bussiness with extensive impact on Thailand, both with respect to quality of life of its citizen and all sectors of its economy --- especially the tourism sector. Such vendors are often unhygienic and untidy which undermines health and well-being of citizens and tourists alike. This innovative research aimed to develop an operational model of Thai street food enterprises that integrates the network of related parties including both public and private. This study was conducted between 15th of March 2018 and 31st of August 2019 on the existing operations of both places and persons involved with street food vending. As sample locations, 12 venues with good management were selected from across the country by local health centers. The study was conducted through organising local workshops and focus group discussions with personnel and excutives from various groups including department of health, provincial health office, municipality and local administrations, and representative of restaurant and street food vender associations. Data collected were analysed to identify the developmental history, management characteristics, key success factors, and opporunities for further improvement at each location. Then, together with documentary research of laws, academic theories and norms, an operational model was proposed: at the community-level, there were 4 principal components of operations --- infrastructure, human resource, finance, and operationalsystem --- that had to be considered. At the town-level, one should aim to follow the conceptual framework for “healthy city” as recommended by the World Health Organization. This operational model of Thai street food enterprises should be implemented in all provinces to fulfill the 2020 governmental policy of improving people’s quality of life and support sustainable tourism.